A prospective pilot study of a gluten‐free diet for primary sclerosing cholangitis and associated colitis. Issue 2 (20th October 2022) - Liwinski, Timur; Hübener, Sina; Henze, Lara; Hübener, Peter; Heinemann, Melina; Tetzlaff, Marcus; Hiller, Marie I.; Jagemann, Bettina; Surabattula, Rambabu; Leeming, Diana; Karsdal, Morten; Monguzzi, Erika; et al.
Summary: Background: Primary sclerosing cholangitis (PSC) is a progressive bile duct disease associated with inflammatory bowel disease (PSC‐IBD). Aim: To investigate whether patients with PSC‐IBD benefit from a gluten‐free and amylase trypsin inhibitor (ATI)‐free diet (GFD). Methods: We performed a prospective clinical pilot study administering an eight‐week GFD. The primary outcomes were colonic inflammation assessed by proctosigmoidoscopy, and liver stiffness (surrogate for fibrosis, inflammation and cholestasis) measured by transient elastography before and after GFD. Amongst the secondary (exploratory) outcomes were colonic mucosal and serum cytokine/chemokine changes, the intestinal microbiome and transcriptome dynamics, and shifts in serum markers of hepatic fibrogenesis. Results: Fifteen patients with PSC‐IBD completed the study. The study did not meet its primary outcome: the endoscopic score and liver stiffness remained unchanged. However, the expression of pro‐inflammatory mucosal cytokines and chemokines such as IL6, IL8, CCL2, and TNFα was significantly down‐regulated. Two critical markers of liver fibrosis and matrix remodelling, thrombospondin‐2 and ‐4, decreased significantly. The microbiota composition changed slightly, including a decrease in the pathogen Romboutsia ilealis . The intestinal transcriptome indicated a gut barrier improvement. Pruritus, fatigue, overall well‐being, faecal calprotectin levels, and serum alkaline phosphatase did not change significantly. Conclusions: This study did not demonstrate a clinical improvement with short‐term GFD in patients with PSC‐IBD. However, a gluten/ATI‐free diet may improve biomarkers of intestinal inflammation and barrier function in these patients with associated changes in the enteric microbiota. Further investigation of the therapeutic potential of the GFD in PSC‐IBD is warranted. Abstract : Effects of a gluten/ATI‐free diet in patients with PSC‐IBD.